2023
DOI: 10.1101/2023.07.29.551099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community structure of heritable viruses in aDrosophila-parasitoids complex

Julien Varaldi,
David Lepetit,
Nelly Burlet
et al.

Abstract: The diversity and phenotypic impacts related to the presence of heritable bacteria in insects have been extensively studied in the last decades. On the contrary, heritable viruses have been overlooked for several reasons, including technical ones. This is regrettable because of the size of this gap knowledge and because case study indicate that viruses may have profound impact on the functionning of individuals and communities. Additionally, the factors that may shape viral communities are poorly known, except… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Throughout evolution, endoparasitoid wasps have maintained a special relationship with viruses. This is evident not only from the abundance and diversity of "free-living" heritable viruses that are injected during oviposition into their hosts [46], [17], [85], [20], [86,36] but also from the abundance of endogenous viral elements found in their genomes. In line with this idea, it was recently found that Hymenoptera with an endoparasitoid lifestyle had a higher propensity to endogenize (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout evolution, endoparasitoid wasps have maintained a special relationship with viruses. This is evident not only from the abundance and diversity of "free-living" heritable viruses that are injected during oviposition into their hosts [46], [17], [85], [20], [86,36] but also from the abundance of endogenous viral elements found in their genomes. In line with this idea, it was recently found that Hymenoptera with an endoparasitoid lifestyle had a higher propensity to endogenize (i.e.…”
Section: Introductionmentioning
confidence: 99%